Twenty-five-year trends in myocardial infarction attack and mortality rates, and case-fatality, in six European populations - Dégano, Irene R; Salomaa, Veikko; Veronesi, Giovanni; Ferriéres, Jean; Kirchberger, Inge; Laks, Toivo; Havulinna, Aki S; Ruidavets, Jean-Bernard; Ferrario, Marco M; Meisinger, Christa; Elosua, Roberto; Marrugat, Jaume (Heart (British Cardiac Society), 2015)
ObjectiveDue to the burden of coronary heart disease (CHD), the monitoring of CHD trends is required. This study sought to examine the acute myocardial infarction (AMI) trends in attack and mortality rates, and in 28-day case-fatality, in six European populations during 1985–2010.MethodsData consisted of 78 128 AMI events included in eight population-based registries from Finland (several populations), Italy (Brianza and Varese), Germany (Augsburg), France (Haute-Garonne), Spain (Girona) and Estonia (Tallinn). AMI event rates and case-fatality trends were analysed using the annual percentage change (APC) obtained by negative binomial and joinpoint regression.ResultsAMI attack and mortality rates decreased in most populations. Finland experienced the steepest decline in attack rates (APC=−4.4% (95% CI −5.1 to −2.9) in men; −4.0% (−5.1 to −2.8), in women). Total-hospital and inhospital case-fatality decreased in all populations except in Tallinn. The steepest decline in total case-fatality occurred in Spain (−3.8% (−5.3 to −2.4) in men; −5.1% (−6.9 to −3.3) in women). Prehospital case-fatality trends differed significantly by population and sex. The trends for all included populations showed a significant decline in AMI event rates and case-fatality, in both sexes and all age groups. However, in women aged 65–74 years, a significant increase in total case-fatality occurred in 2005–2010 (4.7% (0.7 to 8.8)).ConclusionsAMI event rates and inhospital case-fatality declined in 1985–2010 in almost all populations analysed. Prehospital case-fatality declined only in certain population groups, showing differences by sex. These results highlight the need of specific strategies in AMI prevention for certain groups and populations.